EFEKTIVITAS PENGGUNAAN MEDIA VIDEO STOP MOTION TERHADAP HASIL BELAJAR PESERTA DIDIK MATERI FLUIDA STATIS - Parsimin Parsimin; Stepanus Sahala Sitompul; Syukran Mursyid (Universitas Tanjungpura, 2021)
AbstractThis study aims to determine whether the use of stop motion video media can improvestudent learning outcomes on static fluid material. This research was the quantitativemethod. The design of this research was quasi experimental with the nonequivalent controlgroup. The total number of students in this study was 32, with 19 in the experimental classand 13 in the control class.. Statistical analysis used is a logical test to test the validity andCronbach's Alpha to test the reliability of the instrument. Shapiro Wilk's method to test thenormality of the data, Levene's test to test the homogeneity. Meanwhile, to test the hypothesisusing paired sample t test, independent sample t test and one sample t test. All calculationswere processed using the SPSS version 25 program. Hypothesis test paired sample t test,obtained a significance value of 0.00 < 0.05. It can be concluded that there is an effect ofusing stop motion video media on improving student learning outcomes. Independent samplet test, obtained a significance value of Equal variances assumed < Equal variances notassumed (0.235 < 0.294). It can be concluded that there are differences in learningoutcomes between the experimental class and the control class. One sample t test, obtaineda significance value of 0.014 < 0.05. It can be concluded that stop motion video media iseffective for student learning outcomes.Keywords: Effectiveness, Media, Learning Outcomes